Fetal vulvar cysts with spontaneous resolution. (13th October 2014) - Sá, Maria Isabel; Rodrigues, Ana Isabel; Ferreira, Luisa; Rodrigues, Maria do Céu
Abstract : Congenital anomalies of the external genitalia occur in 2–3 per 100 infants. These anomalies might bring variable degrees of morbidity to the infant and often constitute diagnostic challenges for health professionals. We present a case report of a fetus with bilateral vulvar cysts diagnosed during the third trimester ultrasound. The cysts spontaneously regressed before birth and the newborn showed no genital anomalies at birth.